(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The recent addition of China’s market economy less than 20 years ago, has already become the world’s biggest exporter. Its special appeal in costs and potential market have led it to become the first recipient of international foreign investment. Chinese culture and the complex interaction with Western companies has created distortions in business relationships, including with Spanish companies. The article discusses the differences between Spanish and Chinese culture in a business environment, by using methods of analysis from authors with specialized models in multicultural comparison. Conclusions gather suggestions helping to understand the cultural principles and serving as a roadmap for the Spanish entrepreneur operating in China, thereby facilitating cross-cultural management.